Free convection from a heated vertical cylinder with variable surface temperature - Quek, Jian Ting (2016)
This report discuss the literature studies and numerical analysis of a heated vertical cylinder subjected to variable surface temperature undergoing free convection flow. Surface wall temperature is considered to be proportional to x^n, where x is the distance from the base along the vertical axis and n is a constant. This problem and its governing equations was originated from J.J.Shu and I.Pop , thus this report will serve as a continuation to their study. Several studies related to free convection had been conducted in past recent years where most authors analysed either uniform or variable wall temperature. No studies compared the solutions between the two different conditions, thus this report will showcase the results of the comparisons. Firstly, discussion of past researches were made and the relation with conservation of laws with convection equation were shown clearly. Secondly, this report present a numerical analysis by using a software 'MATLAB' for computation where it generate the solutions by iterations. The solutions will then be plotted into various graphs for easy comparisons between the relationship for different parameters such as, Prandtl number, stretched streamwise coordinates and constant n . While presenting the solution, discussions for the results on the effect of different parameters affecting the transfer of heat will be presented. Lastly, comparisons within both uniform and variable temperature conditions were made, followed by a conclusion and recommendations for this paper.